Cancer–stroma interactions as a target for cancer treatment. - Alekseenko, I.V.; Pleshkan, V.V.; Sverdlov, E.D. (Інститут молекулярної біології і генетики НАН України, 2018)
During tumor evolution, cancer cells use the tumor-stroma crosstalk to reorganize the microenvironment for maximum robustness of tumor. The success of immune checkpoint therapy generates a new cancer therapy paradigm: an effective cancer treatment should not aim to influence the individual components of super complex intracellular interactomes (molecular targeting), but rather to disrupt the intercellular interactions between cancer and stromal cells, thus breaking the tumor as a whole. In this minireview we consider cancer associated fibroblasts (CAF) and their interactions with cancer cells as a promising direction for cancer therapy.